Enhancing the taste of raw soy sauce using low intensity ultrasound treatment during moromi fermentation. (15th November 2019) - Gao, Xianli; Zhang, Junke; Liu, Ermeng; Yang, Mingquan; Chen, Sui; Hu, Feng; Ma, Haile; Liu, Zhan; Yu, Xueting
Highlights: Sonication elevated taste compounds of soy sauce and lowered its NaCl content. Sonication improved sensory quality of soy sauce and accelerated its maturation. Sonication enhanced enzyme activities and reaction sites of moromi. Abstract: Sonication can significantly enhance amino acids (AAs) release to accelerate maturation during short-term and low-salt soy sauce fermentation. Here, sonication was applied at 68 kHz (60 W/L/10 min/8 circles) to determine its effects on the taste during long-term and high-salt soy sauce fermentation. The possible mechanisms were explored by analyzing differences in enzymes profile, proximate indices, molecular weight distribution of peptides, AAs composition and microstructures of sonicated moromis and their controls. Sonication greatly elevated levels of organic taste compounds ranging from 8.4% to 22.2%, but lowered levels of NaCl (6.0%), peptides ≤ 1 kDa (5.2%), histidine (20.5%) and glutamic acid (3.4%). Compared to its controls, sonicated raw soy sauces also had a more harmonious and palatable taste. Increased enzymes' activities and formation of more surface area and reaction sites in sonicated moromis might be the possible mechanisms for sonication to elevate levels of taste compounds and sensory quality of soy sauce.